STUDI LITERATUR: PENGARUH POLA ASUH PERMISIF TERHADAP KENAKALAN REMAJA DI SURABAYA - Maryuti, Ira Ayu (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2023)
Juvenile delinquency is criminal behavior committed by young people which is a symptom of social illness in children and adolescents caused by a form of social neglect, so that they develop into a form of behavior that deviates from the norms that apply in public. This literature study was conducted to review articles with the aim of identifying the effect of permissive parenting on juvenile delinquency in Surabaya. Data collection in the form of articles was carried out through the Google Scholar database with a focus on juvenile delinquency in Sutrabaya and parenting parents on adolescents in Surabaya and found 15,000 articles, but only 4 articles were relevant to the inclusion criteria. Four (4) articles were found after analyzing the data according to the inclusion criteria with the 2017-2023 publication period. The literature study conducted shows that there is an influence of permissive parenting on juvenile delinquency in Surabaya. Permissive parenting can significantly influence juvenile delinquency in Surabaya.